2011
DOI: 10.1212/wnl.0b013e318227b1b0
|View full text |Cite
|
Sign up to set email alerts
|

Event-related potential markers of brain changes in preclinical familial Alzheimer disease

Abstract: Objectives: Event-related potentials (ERPs) can reflect differences in brain electrophysiology underlying cognitive functions in brain disorders such as dementia and mild cognitive impairment. To identify individuals at risk for Alzheimer disease (AD) we used high-density ERPs to examine brain physiology in young presymptomatic individuals (average age 34.2 years) who carry the E280A mutation in the presenilin-1 (PSEN1) gene and will go on to develop AD around the age of 45.Methods: Twenty-one subjects from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 39 publications
3
33
1
Order By: Relevance
“…These differences were more pronounced during the (200-300) ms period. Discriminant analysis at this time interval showed promising sensitivity (72,7 %) and specificity (81,8 %) for predicting the presence of AD (Y T Quiroz et al, 2011).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…These differences were more pronounced during the (200-300) ms period. Discriminant analysis at this time interval showed promising sensitivity (72,7 %) and specificity (81,8 %) for predicting the presence of AD (Y T Quiroz et al, 2011).…”
Section: Discussionmentioning
confidence: 91%
“…Recordings were obtained while subjects performed a memory encoding task using color pictures of concrete and nameable objects ( Figure 1). This task is based on a paradigm previously used in the same population (Y T Quiroz et al, 2011). 50 stimuli were presented.…”
Section: Eeg Recordingsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in individuals with mild cognitive impairment (MCI), reductions in sensor-space N400 (see below) or P600 word repetition effects are associated with greater likelihood of subsequent transition to AD dementia [6]. Using EEG data from the Colombian kindred, Quiroz et al [7] found differences in sensor-space event-related potentials (ERPs) between a Presymptomatic Carrier (PreC) group (carrying the PSEN1 mutation) and a Non-Carrier (NonC) group. The PreC group showed less positivity in frontal regions and more positivity in occipital regions compared to NonCs.…”
Section: W Penny Et Al / Dynamic Causal Modeling Of Preclinical Eegmentioning
confidence: 99%
“…Neurotoxic amyloid-β is a peptide generated via cleavage of amyloid-β precursor protein (APP) by the γ-secretase complex. Presenilins are catalytic members of the complex, and mutations in the presenilin gene are the major cause of familial AD (2). Presenilin is involved in several biological functions, but is well known for its role in the generation of the amyloid-β peptide in AD.…”
Section: Introductionmentioning
confidence: 99%